Menumbuhkan Pemahaman Seksualitas Yang Positif Bagi Remaja Melalui Edukasi Seksual di MTS Subulus Salam Semboro - Rey Dhiemaz G. P; Siti Mufikatus S; Hasna’ Huwaida (Indonesian Journal Publisher, 2024)
Adolescence is an important transition period with many physical, cognitive, and social changes. During this time, sexual education is important to help adolescents understand their development, build healthy relationships, and avoid risky sexual behavior. This activity aims to foster knowledge related to healthy sexuality and how to recognize sexuality at the adolescent stage. This activity was carried out with the results of interviews with students and students at MTs Subulus Salam Sidomulyo Semboro sub-district which indicated that students and students still lacked understanding about protecting reproductive organs, understanding the definition of appropriate sexuality, the importance of maintaining sexual health and had never received an understanding of supporting skills during adolescence in maintaining sexual health. Non-training psychoeducation is given to 7th, 8th, 9th and 10th grade MA students to provide knowledge related to sexuality. The implementation of psychoeducation involves Pre-Test and Post-Test to measure changes in students' understanding after the implementation of the activity. Psychoeducational activities carried out at MTs Subulus Salam went well because the audience was quite interactive and enthusiastic when the activity was carried out, and this activity can also be said to be successful with an increase in knowledge which can be seen from the average results of filling out the Pre-test and Post-test where students get an increase in scores from 58 to 95 and there are students who initially 60 to 90.